Studying the physical characteristics and quantity of water flow into the basin Case study: Se Thamok Sub-basin - Anothai , Sakounxay; Xaypanya, Phetyasone; Chanthavongsa, KhamKeng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The Se Thamok sub-basin is a sub-basin that experiences natural disasters almost every year, including floods and droughts, which have caused enormous damage to the environment, property and people's livelihoods. Basic data study and analysis of the physical features of the catchment including analysis of the amount of water flowing into the catchment. The main purpose of this research is to analyze the physical characteristics of the Se Thamok sub-basin area with the ArcGIS 10.5 program; Analyze the distribution of average annual rainfall using the Inverse Distance Weighted (IDW) method and analyze the number of rainy days each year from the daily rainfall data for a period of 30 years (1991-2019) from 03 stations in and around the catchment. Also analyze the maximum amount of flood water flowing into the catchment area in different years with the method of Log Pearson Type III. The research results found that the physical features of the Se Thamok watershed area include 5 featherlike basins and complex basins. Among them, watershed 01 has the largest area covering 509.42 km2 and the smallest area is watershed 03 covering 84.05 km2. The geographical features of the catchment area are very different. The northern area of the catchment area has a relatively high slope, while the middle and southern areas of the catchment area are low flat and mostly clay soil. Including the amount of rainfall has an effect on the flow of water into the catchment, where the maximum rainfall is distributed from the north to the southwest. Land use change is another important factor that influences the occurrence of droughts and floods in many areas of the Se Thamok sub-basin.